Corona virus response: narrative on how the virus transformed lives in the rural areas of Abia state, Nigeria - Enwereji, E. E.; Ezeama, M. C. (International Journal of Advances in Medicine, 2020)
Background: Many people in communities especially children and elderly are at risk of losing their lives to pneumonia, diarrhoeal diseases, malaria, HIV and other preventable diseases unless urgent action is taken to mitigate the spread of COVID-19. For instance, disruptions in immunization services for fear of getting infected with the virus will result in more children dying from pneumonia, which already kills many children in rural areas. Limited resources in rural areas may result to lack of basic hand washing facilities at home which form the fundamental mechanism to prevent COVID-19, thereby, expose already vulnerable people in rural areas to infection. Study assessed the extent to which individuals in rural areas effectively practiced preventive measures of COVID-19 infection as outlined by centre for disease control (CDC). Methods: This is qualitative study that utilized collaborative information from 36 health care professionals under the aegis of members of COVID-19 committee working together in partnership with state government to ensure that best quality services are available to control, prevent and cushion effects of COVID-19 during and after the COVID-19 crisis. This study is therefore, snapshot of activities individuals in rural areas take to prevent COVID-19 infection. Results: Findings showed that preventive measures like lockdown and social distancing rules, wearing of face mask, hand washing with soap, and environmental cleanliness were slightly observed thereby, exposing the rural areas to COVID-19 infection. The study observed that public and private life like sexual life, marital life, income, education, employment and social interaction were negatively affected. Conclusion: From the findings of the study, governments’ financial support during the lockdown was insignificant. Therefore, there is need for the governments to provide social amenities to alleviate the numerous socio-economic problems of individuals in the rural areas.